Організація українських націоналістів і зарубіжні спецслужби (1920 - 1950-ті рр.) - Вєдєнєєв, Д.В.; Лисенко, О.Є. (Інститут історії України НАН України, 2009)
The article characterizes contacts between Organization of Ukrainian Nationalists and particularly S.Bandera with diplomatic and special institutions of other countries. The author analyses foregrounds, forms of collaboration of Security Service of the Organization and special services of different countries during realization of military-political strategy of Ukrainian independent forces.